2009
DOI: 10.1111/j.1365-2133.2009.09225.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic rainbow pattern in non-Kaposi sarcoma lesions

Abstract: Reference1 Cheng ST, Ke CL, Lee CH et al. Rainbow pattern in Kaposi's sarcoma under polarized dermoscopy: a dermoscopic pathological study. Br J Dermatol 2009; 160:801-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 1 publication
(3 reference statements)
0
43
0
Order By: Relevance
“…- for the nail plate examination: longitudinal parallel white lines, longitudinal parallel grey lines, sharply demarcated lesion edges, parallel lesion edges, hairpin vessels, splinter hemorrhages, ‘rainbow sign' [9], and pink coloration of the background;…”
Section: Methodsmentioning
confidence: 99%
“…- for the nail plate examination: longitudinal parallel white lines, longitudinal parallel grey lines, sharply demarcated lesion edges, parallel lesion edges, hairpin vessels, splinter hemorrhages, ‘rainbow sign' [9], and pink coloration of the background;…”
Section: Methodsmentioning
confidence: 99%
“…The rainbow pattern , consisting of multicolored areas showing the colors of a rainbow's spectrum [ 52 ], is not specifi c, as it has been encountered in other conditions (melanoma, stasis dermatitis, lichen planus, and hemosiderotic dermatofi broma) [ 53 ].…”
Section: Kaposi's Sarcomamentioning
confidence: 97%
“…It is commonly accepted that it would be a product of the interaction between polarized light and the "back to back" vessels and, although it was initially described as typical of KS, other authors have found it in lesions such as hemosiderotic dermatofibroma, basal cell carcinoma, pyogenic granulomas, melanomas, stasis dermatitis and lichen planus and others [1,2,7,8].…”
Section: Commentsmentioning
confidence: 99%